The need for monetary reserves - MACHLUP, F. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> The article addresses the question of whether it is possible to find any objective criteria for the need of monetary reserves, either for individual countries or for the world at large. The author first distinguishes between the “need for monetary reserves” and the “demand for international liquidity”. Some of the theories which seek to explain why large reserves are held and considered necessary are examined. In particular, the relations between official reserves and imports, variations of the trade balance, imports and capital outflows, past deficits, domestic money supply and current liabilities are analysed. The author then argues that no particular amount of reserves is needed or adequate. Rather an increase in reserves is needed or adequate to prevent restrictions on foreign trade and payments. Reserves are not needed for any of the purposes emphasized by either theorists or practitioners, but rather are determined by the ambitions of monetary authorities. Moreover, the volume of reserves are not determined by what the authorities want to hold but rather by what they are offered and are willing to accept. Finally, three effects of increases in reserves are highlighted before an application to present-day discussions is provided. JEL: E42, F31, F33 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if gte mso 10]> <![endif]-->